2022
DOI: 10.3390/healthcare10112227
|View full text |Cite
|
Sign up to set email alerts
|

Exploring People’s Knowledge of Genetics and Attitude towards Genetic Testing: A Cross-Sectional Study in a Population with a High Prevalence of Consanguinity

Abstract: This study investigated people’s knowledge of genetics, attitudes toward genetic testing, and views on consanguinity. This cross-sectional study utilized a validated questionnaire modified from published studies to collect data on people’s knowledge of genetics and attitudes about genetic testing among 1008 respondents from various Saudi Arabian regions. Using SPSS software version 26, data were analyzed using a t-test, ANOVA, and multivariate analysis. p-values of <0.05 were considered statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Notably, the awareness of the studied participants in the current research was higher than that reported by Vermeulen et al [ 16 ] in the United Arab Emirates, where only 7% of participants exhibited a good knowledge level in genetics and genomics. Conversely, the results were lower than those reported by Alotaibi et al [ 10 ] in Saudi Arabia, where two-thirds of the participants had sufficient knowledge of genetics. It is important to consider that a significant proportion of the Saudi participants were university students, likely exposed to genetics fundamentals through academic courses, unlike more than half of the participants in the current study, who had primary and secondary education backgrounds.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Notably, the awareness of the studied participants in the current research was higher than that reported by Vermeulen et al [ 16 ] in the United Arab Emirates, where only 7% of participants exhibited a good knowledge level in genetics and genomics. Conversely, the results were lower than those reported by Alotaibi et al [ 10 ] in Saudi Arabia, where two-thirds of the participants had sufficient knowledge of genetics. It is important to consider that a significant proportion of the Saudi participants were university students, likely exposed to genetics fundamentals through academic courses, unlike more than half of the participants in the current study, who had primary and secondary education backgrounds.…”
Section: Discussioncontrasting
confidence: 93%
“…Moreover, the current study found that participants with a higher level of awareness also showed a more positive attitude toward the utilization of genetic services. This correlation between awareness and attitude is consistent with the results reported by Alotaibi et al [ 10 ], emphasizing a positive and significant association between participants' awareness and their attitudes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Knowledge of genetic technology develops individuals' attitudes towards its adoption of technology. The increased understanding of genetics and genetic testing tends to correlate with more positive attitudes toward genetic technology [42][43][44][45][46][47]. This shows that, as individuals become more informed about the scientific principles and applications of genetics, they are more likely to have a favorable view of genetic technology and recognize its potential benefits in various domains, such as healthcare and agriculture.…”
Section: Genomic Knowledge and Attitudes Towards Genetic Technologymentioning
confidence: 99%
“…In the United Arab Emirates, despite the numerous obstacles that women confront, most participants continued to believe in the consanguineous marriage system (8). Data from Saudi Arabia indicated that consanguineous marriages are still common despite them knowing the increased risk of producing children with genetic disorders (9).…”
Section: Introductionmentioning
confidence: 99%